Rationalisation of Nursing Education in Limpopo province: Nurse educators' perspectives - T.R. Makhuvha; M. Davhana-Maselesele; V.O. Netshandama (AOSIS, 2007)
Nursing education institutions are facing a challenge of realigning its functioning according to the changes that are taking place within the country. The intention of the government post apartheid was to correct the imbalances which were brought about by the apartheid government and the following regulations and policies influenced the change in nursing education, that is, Reconstruction and Development Programme (RDP), White Paper on Higher Education (WPHE), and the National Qualification Framework (NQF) (South Africa, 1995:6). In 1996 the government introduced the first democratic constitution of the Republic of South Africa (RS A) according to Act 108 of 1996. In the light of those increasing changes in nursing education, led by political change, the experiences of nurse educators is a critical issue facing nursing campuses. The purpose of this study was two-fold; namely: to explore and describe the experiences of nurse educators with regard to the rationalisation of nursing education and to use information obtained to describe guidelines for the effective rationalisation of a nursing college in the Limpopo Province. A qualitative, exploratory, descriptive and contextual research design was used. Qualitative interviews were conducted with nurse educators who worked in nursing colleges before and after 1994. Measures to ensure trustworthiness were applied and ethical issues were adhered to throughout the research process. Data was analysed following Tesch's method (Creswell 1994:154-155). The research established that nurse educators experienced dissatisfaction in several areas relating to the rationalization of nursing education. Support was also expected from bureaucracy at higher level. This study developed guidelines to policy makers and nurse educators to ensure effective rationalisation process.